Study on nonlinear friction compensation control in the electro-hydraulic servo loading system of triaxial apparatus. (2018) - Sang, Yong; Sun, Weiqi; Wang, Xudong
Nonlinear friction and uncertain disturbance are two of the most important factors affecting the tracking performance and the robustness in the electro-hydraulic servo loading system of triaxial apparatus. In this paper, an iterative learning control (ILC) based sliding mode control (SMC) has been proposed to solve such a problem. A P-type learning function is used to compensate the model of nonlinear friction. The state-space model of the triaxial apparatus is established and the corresponding controller is designed. The controller employs an ILC based SMC of input-output feedback linearisation (IOFL) method to determine the control rule and accomplish the compensation for the nonlinear friction. A Lyapunov method is applied to analyse the condition of convergence in the finite time and the impact acting on the system caused by the control parameters. The simulation results indicate that the tracking performance and the robustness of the system have been remarkably improved.